Environmental Information Systems in Sub-Saharan Africa : From Innovation to Management - Prévost, Yves; Gilruth, Peter (2012)
The development of Environmental Information Systems (EIS) in Sub-Saharan Africa (SSA) in the 1970s and 1980s was slow, in spite of several efforts to introduce the technology. However since 1990, growth has been phenomenal. Whereas, only one or two institutions in each country were previously active in EIS, over 500 EIS related projects are now under way, involving thousands of African experts, plus numerous development partners from non government organizations (NGOs), the private sector, bilateral agencies, and international organizations. Not surprisingly, the number of actors involved in EIS construction is expected to increase even further, until all institutions and organizations involved in environmental management have adopted EIS-related technologies. The EIS concept as know it today emerges from several initiatives to promote the more efficient use of data in environmental management. First, the advent of satellite remote sensing in 1972 gave a new perspective to viewing the earth's resources and led to large data and training subsidies to stimulate the use of first Landsat and then SPOT products. Next came the early environmental applications of remote sensing in Africa, championed by United Nations Environment Programme (UNEP), which used satellite imagery to monitor rangeland dynamics and desertification. The term EIS only came into wide use in the 1990s, concurrent with the advent of natural resource and environment action plans. The concept reflects our growing understanding of the link between environment and development. Thus, environmental information is the data, statistics, and other documents, that enable managers to identify and quantify specific environmental resource categories, and to determine their optimum utilization. Seen in this larger context, an EIS is the institutional and technical response needed to improve the role and benefits of information in environmental management.